The Racist Fact against American-Indians in Steinbeck’s The Pearl - Abbas Abbas (Hasanuddin University, 2020)
the social conditions of Indians as Native Americans for the treatment of white people who are immigrants from Europe in America. This research explores aspects of the reality of Indian relations with European immigrants in America that have an impact on discriminatory actions against Indians in John Steinbeck's novel The Pearl. Social facts are traced through fiction as part of the genetics of literary works. The research method used is genetic structuralism, a literary research method that traces the origin of the author's imagination in his fiction. The imagination is considered a social reality that reflects events in people's lives. The research data consist of primary data in the form of literary works, and secondary data are some references that document the background of the author's life and social reality. The results of this research indicate that racist acts as part of American social facts are documented in literary works. The situation of poor Indians and displaced people in slums is a social fact witnessed by John Steinbeck as the author of the novel The Pearl through an Indian fictional character named Kino. Racism is an act of white sentiment that discriminates against Native Americans, namely the Indian community.